Impact of Cannabidiol and Tamoxifen treatment on cell death and cell survival in breast cancer in vitro - Mahasha, Mahlatse Fortunate (University of the Witwatersrand, Johannesburg, 2024)
The main non-psychotropic component of Cannabis sativa, Cannabidiol (CBD), alleviates breast cancer treatment-associated side effects but its effects with standard therapy remain unclear. In breast cancer, CBD has been shown to exhibit anti-cancer properties by inducing apoptosis and pro-death autophagy. This study aimed to investigate the effects of combined CBD and Tamoxifen treatment on metabolism, cell death, and cell survival mechanisms in luminal-A breast cancer cell lines MCF7 and T47D. The CBD concentration relative to IC50 was established by testing a range of CBD concentrations: 5 μM, 7 μM, and 10 μM, at 24 h, 48 h, and 72 h using the neutral red cell viability assay. The scratch assay was used to determine the effects of the concentrations on migratory capacity. Two models of treatment were used, single-dose treatment (model 1) and daily-replacement treatment (model 2), and appropriate controls were included. Treatment with 2 μM Tamoxifen and 5 μM CBD for 48 h was determined to be the optimal treatment condition. The MTT assay was performed, and the absorbance ratio indicative of cell proliferation was calculated. The ability of the cells to metabolize the drug components was examined through an assessment of CYP450 reductase (CPR) enzyme activity. The mRNA and protein expression levels of three autophagic markers; BECN1, LC3B, and p62, were investigated using qPCR and immunocytochemistry, respectively. Friedman’s Anova (p<0.05) and Kruskal Wallis (p<0.05) post hoc tests were used to statistically analyse the data. Combined CBD and Tamoxifen treatment showed the greatest decrease in the proliferation of MCF7 cells and T47D cells compared with all other treatments across both treatment models, with the daily- replacement treatment model (model 2) showing more efficacy thus suggesting that combined treatment may inhibit cell proliferation. CYP450 enzyme reductase activity was higher in T47D cells compared with MCF7 cells in both treatment models suggesting increased metabolic activity and susceptibility to combined treatment. However, in the daily replacement model, MCF7 cell CPR activity could not be ascertained, suggesting either prodrug availability or reduced CPR activity. Further analysis is required in this regard. For immunolocalization, optimization was conducted in late 2021 and all three antibodies showed clear and expected immunolocalization but when the experiments were repeated early 2022, immunofluorescence was reduced (P62 and BECN1), with LC3B not detectable. P62 and BECN1 were expressed in both MCF7 and T47D cells across both treatment models although BECN1 expression was not sufficient to be quantified and assessed statistically. LC3B protein levels could not be accurately quantified irrespective of the treatment model used. Low amounts of target mRNA in MCF7 cells resulted in undetermined Cq values of LC3B, P62 and BECN1 genes across both treatment models. In T47D cells, Cq values of target genes were determined across both treatment models and the fold change in gene expression indicated that combined CBD and Tamoxifen treatment effectively upregulates target genes albeit not significantly (LC3B, P62 and BECN1) with the single-dose treatment model (model 1) compared with the daily replacement model. Both the immunofluorescence and qPCR experiments would be required to be repeated to ensure conclusive results. The findings of this study nevertheless indicate that combined CBD and Tamoxifen treatment may inhibit tumour growth, but tumour cells may be able to evade cell death pathways resulting in tumour cell survival
A dissertation submitted in fulfillment of the requirements for the Degree of Master of Science in Medicine (MSc. Med) to the Faculty of Health Sciences , Anatomical Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: Cannabidiol; Breast cancer; Tamoxifen.; UCTD; SDG-3: Good health and well-being